ADVANTAGES AND DISADVANTAGES OF THE EURO - MELINDA CENUŞE; IMOLA DRIGĂ (Annals of the University of Petrosani: Economics)
Creating a single European currency has, undoubtedly two great advantages: on the one hand, lower transaction costs resulting from exchanging various national currencies and, on the other hand, removing the uncertainty arising from these exchanges. Mugur Isarescu, the Governor of the NBR, has recently said that the adoption of the euro in 2014 could not be possible, if inflation does not drop a sustainable level in 2010 and 2011. He noted that current experience with the inflation and devaluation of the national currency shows that reducing inflation without improving other indicators is counterproductive. The problem of estimating the main advantages of a single currency and of a monetary union in general is that it is difficult to clearly distinguish them from those resulting from other aspects of economic integration. The success of a monetary integration requires a certain degree of coordination of macroeconomic policies. It is unanimously agreed that if countries cooperate with each other, together they shall have better results than in the case they do not cooperate. In budgetary process local authorities have the right to establish, observe, control, follow and charge municipal taxes. In this process they also have to report local budgets implementation and rectification.